The Role of AI-Powered Chatbots in Telemedicine: Improving Accessibility and Patient Engagement - Karim, Mahit Kumaris; Sharma, Rajesh; Singh , Vikram (International Journal of Technology and Modeling, 2023)
The integration of Artificial Intelligence (AI) in telemedicine has significantly transformed healthcare accessibility and patient engagement. AI-powered chatbots serve as virtual assistants, providing real-time medical guidance, symptom assessment, and appointment scheduling, thereby reducing the burden on healthcare professionals and improving patient experiences. This paper explores the role of AI-driven chatbots in enhancing telemedicine services by analyzing their capabilities in symptom triage, personalized health recommendations, and patient communication. Furthermore, we discuss the advantages and limitations of AI chatbots, focusing on their impact on remote healthcare delivery, data privacy concerns, and user satisfaction. By evaluating recent advancements and real-world applications, this study highlights the potential of AI chatbots to bridge healthcare gaps, particularly in underserved regions. The findings suggest that AI-powered chatbots can enhance healthcare efficiency, improve accessibility, and foster better patient engagement, paving the way for a more inclusive and technology-driven medical ecosystem.